(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
The low entrepreneurship ratio in Indonesia and public health issues related to food preservatives highlight the need for initiatives that promote entrepreneurship and healthy consumption. This community service program, in the context of Increasing Public Nutrition Awareness through Preservative-Free Local Bread Production, aims to empower home-based bakery businesses in rural areas by increasing production capacity, improving marketing strategies, and promoting healthier alternatives to bread without preservatives. The program was implemented through three stages: preparation (needs analysis and development of training materials), implementation (production and digital marketing training, equipment support, branding, and packaging enhancement), and evaluation (monitoring of key performance indicators and partner satisfaction). The results showed significant increases in production volume, sales growth, visual branding, and market expansion. Partners reported increased business confidence and customer interest, especially due to the health-oriented product positioning. In conclusion, the program successfully increased partners’ business capacity and contributed to local economic empowerment by promoting healthy, preservative-free bread products.